Investigating two-phase digestion of grass silage for demand-driven biogas applications: Effect of particle size and rumen fluid addition. (February 2016) - Wall, D.M.; Allen, E.; O'Shea, R.; O'Kiely, P.; Murphy, J.D.
Abstract: High lignocellulose content grass silage was investigated for two-phase digestion (leaching followed by upflow anaerobic sludge blanket (UASB)) for application to demand-driven biogas production. Leaching trials were undertaken investigating the effects of particle size reduction and rumen fluid addition on the hydrolysis and acidogenesis phases. Reducing grass silage particle size to <1 cm was not suited to leaching as particles could not be fully entrained in the system; this was not an issue at >3 cm particle size. Rumen fluid addition increased production of volatile fatty acids (VFA) but reduced pH levels, which subsequently hindered hydrolysis of volatile solids (VS). When electricity demand is low, it is recommended to operate in leach only mode with grass silage particle size >3 cm and with rumen fluid addition; this limits VS destruction to 30% while maintaining a high VFA yield. When electricity demand is high, connection of the UASB generates 61% destruction of VS maximising biogas production. Operation of the SLBR-UASB achieves lower specific methane yields than traditional single-stage digestion but may offer advantages in demand driven biogas systems. Highlights: Particle size >3 cm had the highest volatile solids (VS) destroyed in stable mode. Adding rumen fluid elevated acid production hindering hydrolysis of VS. When electricity demand is low rumen fluid addition restricted VS destruction. When electricity demand is high, connection of UASB increased VS destruction. Overall methane production was less than for a single phase digestion system.